The association between vitamin D status and inflammatory bowel disease among children and adolescents: A systematic review and meta-analysis - Fatahi, Somaye; Alyahyawi, Naseem; Albadawi, Naryman; Mardali, Farzaneh; Dara, Naghi; Sohouli, Mohammad Hassan; Prabahar, Kousalya; Rohani, Pejman; Koushki, Nazanin; Sayyari, Aliakbar; Hosseini, Amir Hossein; Abu-Zaid, Ahmed (Frontiers in Nutrition, 2023)
Aim: Vitamin D deficiency is very common among IBD children. Since there are conflicting results between the association of vitamin D and IBD, we conducted this systematic review to confirm the association of vitamin D with IBD. Method: We conducted a systematic search in Scopus, Cochrane Library, Web of Science, PubMed, Google scholar to find relevant studies. Articles with cross-sectional and case-control designs which reported the association between vitamin D and IBD among children were included. Results: Eventually 9 studies (with 16 effect sizes) reported the mean and SD or median and inter quartile range of serum vitamin D levels in both IBD and control subjects. The random effects meta-analysis revealed that subjects with IBD had -1.159 ng/ml (95% CI: -2.783, 0.464) lower serum vitamin D concentrations compared with their healthy counterparts, but this difference was not significant. Thirteen studies (with 18 effect sizes) including a total of 2602 participants provided information for prevalence of vitamin D deficiency or insufficiency in IBD patients as 44% (95% CI: 0.34 - 0.54) with significant heterogeneity noted among studies (p<0.001; I2=97.31%). Conclusions: This systematic and meta-analysis study revealed that vitamin D deficiency was associated with IBD. Longitudinal studies should be conducted in future to confirm our findings. Large randomized controlled trials assessing the doses of supplementation of vitamin D would provide better understanding of the association between vitamin D and IBD.